1987
DOI: 10.1017/s0317167100037823
|View full text |Cite
|
Sign up to set email alerts
|

Geography, Drinking Water Chemistry, Pesticides and Herbicides and the Etiology of Parkinson's Disease

Abstract: In 1984 we made the first observation of a correlation between early age exposure to rural environment (and drinking well water) and development of idiopathic Parkinson's disease (IPD). 13 These findings were subsequently confirmed elsewhere (Barbeau, 1985 ; 25 Tanner, 1985 26 ). Analysis of all early age onset IPD (EPD) cases born and raised in Saskatchewan revealed that 20 of 22 had exclusively rural exposure during the first 15 years of life. This distribution was significantly different from the general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 18 publications
4
73
1
1
Order By: Relevance
“…PQ is one of the possible herbicides that are involved in PD, since a strong correlation has been found between the incidence of the disease and the amount of PQ used (Lanska, 1997;Liou et al, 1997;Rajput et al, 1987;Ritz and Yu, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ is one of the possible herbicides that are involved in PD, since a strong correlation has been found between the incidence of the disease and the amount of PQ used (Lanska, 1997;Liou et al, 1997;Rajput et al, 1987;Ritz and Yu, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat (1,1'-dimethyl-4,4'-bipyridinium, PQ), is widely used as a non-selective herbicide, and bears structural similarity to 1-methyl-4-phenyl pyridinium (MPP + ). This herbicide adversely impacts on dopamine systems, and a strong geographical overlapping has been found between the incidence of PD and the amount of PQ used (Lanska, 1997;Liou et al, 1997;Rajput et al, 1987;Ritz and Yu, 2000). PQ induces dopaminergic neuronal damage in experimental animals (Corasaniti et al, 1992;Corasaniti et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson's disease (PD), a profound movement disorder resulting from nigrostriatal dopaminergic (DA) system degeneration, has been linked to living in a rural environment, farming, drinking well water, and occupational exposure to agricultural chemicals, suggesting an environmental exposure basis for the disease (Rajput et al, 1987;Semchuk et al, 1992;Liou et al, 1997;Gorell et al, 1998;. Correspondingly, a recent comprehensive study of over 19,000 white male twins showed that genetic heritability is not the basis of sporadic PD with onset over age 50 .…”
Section: Abstract: Dopamine; Striatum; Nucleus Accumbens; Substantiamentioning
confidence: 99%
“…Other studies have demonstrated that drinking well-water and living in a rural setting, both of which may increase exposure to agricultural pesticides, increase the risk of developing PD (Rajput et al, 1986;Barbeau et al, 1987;Rajput et al, 1987;Golbe et al, 1990;Semchuk et al, 1991). In addition, exposure to pesticides used in the home has been linked to PD (Stephenson, 2000).…”
mentioning
confidence: 99%